2015
DOI: 10.1007/s11051-015-3057-7
|View full text |Cite
|
Sign up to set email alerts
|

Eosin Y-sensitized nanosheet-stacked hollow-sphere TiO2 for efficient photocatalytic H2 production under visible-light irradiation

Abstract: Nanosheet (with around 20 nm in thickness)-stacked hollow-sphere TiO 2 was synthesized via a modified solvothermal reaction for different times followed by calcination treatment at different temperatures. After surface modification by different cations (H ? or Fe 3? ) and further sensitization by Eosin Y, the obtained photocatalysts achieved remarkably enhanced H 2 -production activity (about 4.2 times of that for Eosin Y-sensitized P25) and stability under visible-light irradiation. The improved photocatalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…
Owing to the effect of energy band bending, p-type Co 3 O 4 quantum dots sensitized by Eosin Y showed a high and stable photocatalytic activity (B13 440 lmol h À1 g À1 cat ) for water reduction and hydrogen production under visible-light irradiation without any cocatalyst.The dye-sensitized semiconductor (DSS) system for photocatalytic water reduction and hydrogen production is considered to be one of the most promising routes for making efficient use of solar light to produce clean energy. [1][2][3][4] In a typical DSS system, electrons are excited by light from the dye and then transferred to the conduction band (CB) of the semiconductor for reduction reaction. In order to reduce the overpotential of hydrogen evolution and improve reaction efficiency, cocatalysts are usually loaded onto semiconductor catalysts.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Owing to the effect of energy band bending, p-type Co 3 O 4 quantum dots sensitized by Eosin Y showed a high and stable photocatalytic activity (B13 440 lmol h À1 g À1 cat ) for water reduction and hydrogen production under visible-light irradiation without any cocatalyst.The dye-sensitized semiconductor (DSS) system for photocatalytic water reduction and hydrogen production is considered to be one of the most promising routes for making efficient use of solar light to produce clean energy. [1][2][3][4] In a typical DSS system, electrons are excited by light from the dye and then transferred to the conduction band (CB) of the semiconductor for reduction reaction. In order to reduce the overpotential of hydrogen evolution and improve reaction efficiency, cocatalysts are usually loaded onto semiconductor catalysts.
…”
mentioning
confidence: 99%
“…The dye-sensitized semiconductor (DSS) system for photocatalytic water reduction and hydrogen production is considered to be one of the most promising routes for making efficient use of solar light to produce clean energy. [1][2][3][4] In a typical DSS system, electrons are excited by light from the dye and then transferred to the conduction band (CB) of the semiconductor for reduction reaction. In order to reduce the overpotential of hydrogen evolution and improve reaction efficiency, cocatalysts are usually loaded onto semiconductor catalysts.…”
mentioning
confidence: 99%
“…Thus, the light response range of TiO 2 can be effectively expanded by dye sensitization. Dye molecules can deliver photogenerated electrons to the CB of TiO 2 and then the electrons transfer further to participate in reactions [170][171][172]. For example, Shi et al [171] prepared Eosin Y-sensitized nanosheet-stacked hollow-sphere TiO 2 for efficient photocatalytic H 2 production under visible-light irradiation.…”
Section: Dye Sensitizationmentioning
confidence: 99%
“…Dye molecules can deliver photogenerated electrons to the CB of TiO 2 and then the electrons transfer further to participate in reactions [170][171][172]. For example, Shi et al [171] prepared Eosin Y-sensitized nanosheet-stacked hollow-sphere TiO 2 for efficient photocatalytic H 2 production under visible-light irradiation. Vallejo et al [170] reported the enhancement on light absorption and photocatalytic activity over rGO-TiO 2 thin films after they were sensitized by natural dyes extracted from Bactris guineensis (Figure 12).…”
Section: Dye Sensitizationmentioning
confidence: 99%
“…For a dyesensitized photocatalyst, the dye molecules adsorbed on the surface of a semiconductor can be excited after absorbing visible light, thus injecting electrons into the conduction band of the semiconductor. MK2/TiO 2 [33], Eosin Y/TiO 2 [34], N749/rGO [35], GS12/TiO 2 [36], PY-1/g-C 3 N 4 [37], PY-2/g-C 3 N 4 [37], ZnPy/g-C 3 N 4 [38], chlorin e6/g-C 3 N 4 [39], protoporphyrin/g-C 3 N 4 [40], mTHPC/g-C 3 N 4 [41], Ppa/g-C 3 N 4 [42], N3/g-C 3 N 4 [31], and N719/g-C 3 N 4 [31] exhibited enhanced performance in H 2 evolution. How-Processes 2021, 9, 1055 2 of 15 ever, more studies are needed to enrich the family of dye-sensitized g-C 3 N 4 , to find more efficient catalysts for water splitting, and to understanding fundamental aspects of these photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%